Need for effective feedback within an organisation - Gulati, Aashish (2022)
This management project delves into the current industry-wide practices of feedback within an organisation and how they are influencing and contributing to an employee’s motivation and performance enhancement. Works from many researchers have established that feedback is considering an important communication tool but misses to identify the periodicity, that is, how often should feedback be provided. Normally, every organisation has an annual appraisal which primarily presents the opportunity of a recorded exchange of performance for any employee. The paper tries to ascertain if formal feedback is sufficient to gauge employee motivation and performance once a year. Another important aspect of feedback in an organisation is the direction of feedback. Conventionally, feedbacks are provided by Managers (N) to their direct employees (N-1), that is, top to bottom, however, this management paper explores two-way feedback, that is, N-1 feedback to N.